2019
DOI: 10.2147/ndt.s190477
|View full text |Cite
|
Sign up to set email alerts
|

<p>The association of neutrophil-to-lymphocyte ratio and delayed cerebral ischemia in patients with aneurysmal subarachnoid hemorrhage: possible involvement of cerebral blood perfusion</p>

Abstract: Background and purpose: Emerging evidence suggests that systemic inflammation is associated with the pathophysiological process of delayed cerebral ischemia (DCI) after aneurysmal subarachnoid hemorrhage (aSAH). This study aimed to investigate the association of white blood cell (WBC) count and neutrophil-to-lymphocyte ratio (NLR) with the occurrence of DCI in SAH patients. Methods: A total of 122 patients diagnosed with aSAH within 72 h of onset were retrospectively enrolled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 23 publications
0
30
0
Order By: Relevance
“…Only four studies [ 16 , 24 , 26 , 27 ] provided enough data of peripheral WBC and were included in the meta-analysis to determine the associations between early elevated WBC and occurrence of DCI. Substantial heterogeneity was found among the four studies ( Q statistic = 13.691, I 2 = 78.089%, P = 0.003).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only four studies [ 16 , 24 , 26 , 27 ] provided enough data of peripheral WBC and were included in the meta-analysis to determine the associations between early elevated WBC and occurrence of DCI. Substantial heterogeneity was found among the four studies ( Q statistic = 13.691, I 2 = 78.089%, P = 0.003).…”
Section: Resultsmentioning
confidence: 99%
“…It is known that the need for special laboratory test or collection of CSF sample limits the clinical utility of a biomarker, and this highlights the need for searching for a quick, sensitive and safe biomarker which is easy to obtain for evaluating prognosis in aSAH. In addition, there is increasing evidence on the role of inflammation in the pathogenesis of DCI and poor outcomes following aSAH [ 27 ]. Among the common readily available markers for systemic inflammation, many studies have investigated the independent role of early increase in CRP and WBC as risk factors for unfavorable outcomes after aSAH.…”
Section: Discussionmentioning
confidence: 99%
“…NLR has previously been reported to be useful as a prognostic factor in acute ischemic stroke and transient ischemic attack [36,37]. Recently, Wu et al reported that leukocytosis may be regarded as an early pathology of subarachnoid hemorrhage and that NLR may be used as a practical predictor for the occurrence of delayed cerebral ischemia in those patients [38]. A disturbance in peripheral blood lymphocyte subsets has been described to be associated with complications in high-risk vascular patients [39].…”
Section: Discussionmentioning
confidence: 99%
“…These are enzymes able to degrade any component of the extracellular matrix and play role in brain‐barrier damage and development of secondary brain injury 27 . In addition, the mechanism of NLR‐induced bleeding may be contributed by multifactorial pathophysiology, such as inflammatory reaction, immune dysfunction, and the production of reactive oxygen species (ROS) 5,28‐32 . aSAH can induce the leukocytosis and increased neutrophils by stimulating the systemic cellular responses that can cause the brain injury and delayed cerebral ischemia 33,34 .…”
Section: Discussionmentioning
confidence: 99%
“…27 In addition, the mechanism of NLRinduced bleeding may be contributed by multifactorial pathophysiology, such as inflammatory reaction, immune dysfunction, and the production of reactive oxygen species (ROS). 5,[28][29][30][31][32] aSAH can induce the leukocytosis and increased neutrophils by stimulating the systemic cellular responses that can cause the brain injury and delayed cerebral ischemia. 33,34 Early studies showed that the growth and rupture of cerebral aneurysms were promoted via the leukocyte infiltration and inflammatory reaction in the wall of aneurysms.…”
Section: F I G U R E 2 Roc Curve Of the Prognosis In Patients With Aashmentioning
confidence: 99%